(untitled) (Research, Society and Development, 2021)
Objective: Describe the theoretical foundation process for the construction of 2 (two) Standard Operating Procedures focused on mitigation measures for immediate Transfusional Reactions. Methodology. This is a theoretical study with qualitative, descriptive and exploratory characteristics, which was immersed in national and international specialized literature to support the production of a Standard Operating Procedure aimed at mitigating measures of immediate Transfusion Reactions, developed between the months from March to July 2020, carried out at a University Hospital in Sergipe, based on the weaknesses of the process pointed out in the literature and in labor practice. It was taken into account that TRs can result from three conditions: donor, patient and care provided. Results. The process of constructing the instrument took place in three stages: in the first, it consisted of a review of the literature in order to find qualified and updated scientific evidence on the studied topic; in the second, the entire blood transfusion process in the hospital was analyzed; and in the third, the records and/or notes about the procedural and labor weaknesses observed as demands of health professionals were gathered. need to notify, explain the weaknesses of the process with those involved so that communication and patient identification are allied, monitoring the effectiveness and preventive measures optimized in the management.